Predicting Patterns of Regulatory Behavior in the Still‐Face Paradigm at 3 Months. (15th April 2019) - Barbosa, Miguel; Beeghly, Marjorie; Gonçalves, Joana L.; Moreira, João; Tronick, Edward; Fuertes, Marina
Abstract : The current study addressed two aims: (1) to describe different patterns of infant regulatory behavior during the Face‐to‐Face Still‐Face (FFSF) paradigm at 3 months of age and (2) to identify specific, independent predictors of these patterns from an a priori set of demographic, infant (e.g., temperament), and maternal (e.g., sensitivity) variables. Analyses were based on data collected for 121 mother–infant dyads assessed longitudinally in the newborn period and again at 3 months. In the newborn period, infants' neurobehavior was evaluated using the Neonatal Behavioral Assessment Scale (NBAS) and mothers reported on their caregiving confidence and their newborns' irritability and alertness. At 3 months, mothers reported on their infant's temperament, and mother–infant interactions were videotaped during free play and the FFSF. Three patterns of infant regulatory behavior were observed. The most common was a Social‐Positive Oriented Pattern, followed by a Distressed‐Inconsolable Pattern, and a Self‐Comfort Oriented Pattern. Results of multinomial logistic regression indicated that categorical assignment was not associated with demographic or infant characteristics, but rather with dyadic regulatory processes in which maternal reparatory sensitivity played a crucial role.